Petronius and the anatomy of fiction - Rimell, Victoria (Cambridge University Press, 2002)
Usually seen just as an index of the 'low' genre of Petronius' Satyricon, corporeality is here for the first time explored as a metaphor and it is argued that, on the level of imagery, the text can be read as a unified whole rather than as an episodic jumble.